Prosthodontic rehabilitation of AIDS Patients: An Overview - Y K Singla; Ashish Bali; Atinderpal Singh (Wolters Kluwer Medknow Publications, 2018)
Procurement for high standard of oral hygiene is a cardinal requirement for any individual and dentists constantly aim to provide optimal treatment to their patients. However, when it comes to treat patients with immunocompromised diseases, particularly those attached with social stigma like AIDS/HIV, there remain doubts and hesitations. This may lead the dentists to break the ethical responsibility by abjuring or not providing adequate treatment to these patients. Such situations can easily be avoided with absolute knowledge and awareness among the oral health-care providers including prosthodontist regarding the disease process, its connotations and measures to be taken during their treatment. This article summarizes the fundamental points in the prosthodontic management of immunocompromised patients which in the opinion of the author may be easily consolidated in dental practice.